The Debate in the DNA Cases Over the Foundation for the Admission of Scientific Evidence: The Importance of Human Error as a Cause of Forensic Misanalysis - Edward J. Imwinkelried (Washington University Law Quarterly, 1991)
The first part of the Article addresses the threshold question of whether deficiencies in test protocol should affect the admissibility as well as the weight of scientific testimony. After surveying the empirical studies of laboratory proficiency, the Article concludes that correct test procedure is such a fundamental concern that it should impact the admissibility of scientific evidence. The second part of the Article turns to the question of whether the proponent or opponent should be allocated the burden of showing the analyst's compliance with proper scientific protocol. Analogizing to Federal Rule of Evidence 803(8) governing the hearsay exception for official records, the Article advances the novel proposal that the party opposing the admission of scientific testimony should be assigned the burden on this issue.
Keywords: Human error; DNA fingerprinting